2023
DOI: 10.1007/s12672-023-00809-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between Ki67 expression level and neoadjuvant treatment response and prognosis in breast cancer based on the Neo-Bioscore staging system

Yurdanur Sullu,
Leman Tomak,
Guzin Demirag
et al.

Abstract: Background Neoadjuvant chemotherapy (NAC) is widely used in the treatment of primary breast cancer. Different staging systems have been developed to evaluate the residual tumor after NAC and classify patients into different prognostic groups. Ki67, a proliferation marker, has been shown to be useful in predicting treatment response and prognosis. We aimed to investigate the prognostic importance Neo-Bioscore stage and pretreatment and posttreatment Ki67 levels in breast cancer patients who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Similarly, Fasching et al [21] reported that Ki67 has independently predicted treatment response and prognosis in breast cancer patients. Luminal breast cancer exhibits a variable Ki67 score; Luminal A is typically associated with low scores, whereas Luminal B generally shows the opposite [22]. Kim et al [24] published a study investigating the potential bene ts of NACT in clinically node-positive luminal subtype breast cancer, particularly regarding the facilitation of breast-conserving surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Fasching et al [21] reported that Ki67 has independently predicted treatment response and prognosis in breast cancer patients. Luminal breast cancer exhibits a variable Ki67 score; Luminal A is typically associated with low scores, whereas Luminal B generally shows the opposite [22]. Kim et al [24] published a study investigating the potential bene ts of NACT in clinically node-positive luminal subtype breast cancer, particularly regarding the facilitation of breast-conserving surgery.…”
Section: Discussionmentioning
confidence: 99%